Government Debt, Government Spending, and Private Sector Behavior: Comment - Barth, James R.; Iden, George; Russek, Frank S. (American Economic Review, 2016)
In a recent issue of this Review (1983), Roger Kormendi relied upon the work of Martin Bailey (1962, 1971) and Robert Barro (1974) develop an alternative to modeling private sector consumptionsaving behavior based on rational evaluation of the consequences of government fiscal policy (p. 995). Briefly, this involves determining to what extent government spending substitutes for private consumption, and to what extent government debt is net wealth and thereby also affects private consumption. This consolidated approach to examining private sector consumption is not only novel, but appears at a time when there is widespread interest as well as controversy over the effects of government fiscal policy. It therefore seems only appropriate to examine further the results obtained by Kormendi-not to criticize them but rather to explore their robustness. This comment specifically explores the sensitivity of Kormendi's results to alternative time periods of estimation, to the differentiation between federal debt and state and local government debt, and to the measurement of government debt-particularly par vs. market value.